It's not just about protein turnover: the role of ribosomal biogenesis and satellite cells in the regulation of skeletal muscle hypertrophy - Brook, M. S.; Wilkinson, D. J.; Smith, K.; Atherton, P. J. (European Journal of Sport Science, 2019)
Skeletal muscle has indispensable roles in regulating whole body health (e.g. glycemic control, energy consumption) and, in being central in locomotion, is crucial in maintaining quality-of-life. Therefore, understanding the regulation of muscle mass is of significant importance. Resistance exercise training (RET) combined with supportive nutrition is an effective strategy to achieve muscle hypertrophy by driving chronic elevations in muscle protein synthesis (MPS). The regulation of muscle protein synthesis is a coordinated process, in requiring ribosomes to translate mRNA and sufficient myonuclei density to provide the platform for ribosome and mRNA transcription; as such MPS is determined by both translational efficiency (ribosome activity) and translational capacity (ribosome number). Moreover, as the muscle protein pool expands during hypertrophy, translation capacity (i.e. ribosomes and myonuclei content) could theoretically become rate-limiting such that an inability to expand these pools through ribosomal biogenesis and satellite cell (SC) mediated myonuclear addition could limit growth potential. Simple measures of RNA (ribosome content) and DNA (SC/Myonuclei number) concentrations reveal that these pools do increase with hypertrophy; yet whether these adaptations are a pre-requisite or a limiting factor for hypertrophy is unresolved and highly debated. This is primarily due to methodological limitations and many assumptions being made on static measures or correlative associations. However recent advances within the field using stable isotope tracers shows promise in resolving these questions in muscle adaptation.